Copper extraction from the sulphation-roasted copper technogen concentrate (Bulletin of the Institute of Chemistry and Chemical Technology, 2022)
The technogen concentrate containing copper sulfide was obtained by alkaline-sulfide leaching of tetrahedrite concentrate with Bi, Sb, and As contamination. The technogen concentrate which contains Cu-33.45%, Fe-14.14%, Ag-0.73%, and S-23.87% were sulphation roasted under air, and the optimum condition of copper extraction from the roasted product was studied. According to the XRD and SEM-EDS analysis, the roasted residue obtained by the sulphation roasting at lower temperatures contains copper sulfate and associated minerals such as goethite, hematite, and magnetite. The elemental composition of the roastedproduct is confirmed as Cu 28.12%, Fe 20.52%, Ag 0.65%, and S 14.34% when analyzed by ICP-OES and chemical analysis. This roasted product containing the copper compounds was easily soluble in water and sulfuric acid. The leaching parameters such as solvent concentration, temperature, leaching time, solid-liquid ratio, and stirring rate were studied systematically. Under the optimized condition of water (25°C, 500 rpm, 1:50, 60 min) and sulfuric acid (1.6 М H2SO4, 25°C, 200 rpm, 1:8, 60 min) leaching, 91.68% and 97.19% copper were recovered in the solution while leaching residue contains 61.47% and 29.18% of iron, respectively. The leaching residue also contains hematite, goethite, maghemite, and albite as revealed in the XRD analysis. The leaching process of copper compounds is found to occur by diffusion both in the water and acid leaching, and activation energy is calculated as 6.05 and 8.70 кJ/mol, respectively.Зэсийн техноген баяжмалыг сульфатжуулан шатааж, зэс ялгаж авах боломжХураангуй: Тетраэдритийн баяжмал дахь Bi, Sb, As-ийг шүлт-сульфидын холимогт уусгахад зэсийн сульфид (халькопирит, ковеллин, халькозин ба пирит) агуулсан хатуу үлдэгдэл буюу зэсийн техноген баяжмал үүсдэг. Техноген баяжмалд Cu-33.45%, Fe-14.14%, Ag-0.73%, S-23.87% агуулагдана. Түүнийг агаарын орчинд сульфатжуулан шатаах, зэсийг уусгах тохиромжтой горимыг тогтоох судалгааг хийв. Зэсийн техноген баяжмалыг нам температурт сульфатжуулан шатаахад үүссэн дээжийг XRD, SEM-EDS-ээр шинжлэхэд зэсийн сульфат давамгайлж, гётит, гематит, магнетит илрэв. Шатаасан дээжний найрлаганд Cu-28.12%, Fe-20.52%, Ag-0.65%, S-14.34% агуулагдаж буйг ICP-OES болон химийн шинжилгээний аргаар тодорхойлов. Хатуу үлдэгдлийг сульфатжуулан шатаахад ус болон хүхрийн хүчил (H2SO4)-ийн уусмалд хялбар уусдаг зэсийн нэгдлүүд үүсдэг байна. Тэдгээрийн уусалтанд нөлөөлөх уусгагчийн концентраци, температур, хугацаа, хатуу ба шингэн фазын харьцаа, хутгах хурд зэрэг үзүүлэлтүүдийг судалсан. Уусгалтын дүнгээс үзэхэд ус (25 °C, 500 эрг/мин, 1:50, 60 мин) болон хүчлийн (1.6 М H2SO4, 25 °C, 200 эрг/мин, 1:8, 60 мин) уусгалтын оновчтой нөхцлүүдэд Cu харгалзан 91.68% ба 97.19% хүртэл уусмалд шилжиж, хатуу үлдэгдэлд Fe-61.47% ба 29.18% агуулагдаж байна. Үүнээс гадна XRD-ийн шинжилгээгээр гематит, гётит, маггемит, альбит илэрсэн. Зэсийн нэгдлүүдийн ус болон хүчилд уусах уусалтын процесс нь диффузийн зүй тогтлоор явагдаж байгааг тогтоон, идэвхжилийн энергийг харгалзан 6.05 ба 8.70 кЖ/моль гэж тооцоолов.Түлхүүр үг: уусгалт, кинетик, зэсийн сульфидүүд